The Convertible Note Mechanism and the Risk of Share Dilution: Legal Protection for Minority Shareholders - Meily Natassya; Gunardi Lie (Lambung Mangkurat Law Journal, 2025)
The convertible note instrument is increasingly being used by startup companies to raise early-stage funding due to its flexibility and efficiency, particularly in deferring company valuation until a subsequent funding round. However, despite its convenience, this scheme entails legal risks, especially for minority shareholders. The debt-to-equity conversion process may lead to shareholding dilution and weaken the bargaining position of minority shareholders within the company’s decision-making structure. This journal examines how the conversion mechanism in a convertible note can lead to share dilution risks and explores the available legal protections for minority shareholders against such risks. This research adopts a normative juridical method with a statutory and literature-based approach, analyzing both legal texts and contractual practices. The findings indicate that although Law No. 40 of 2007 concerning Limited Liability Companies recognizes the right of first refusal (pre-emptive right), Article 43 paragraph (3) exempts this right in the context of the conversion of convertible securities into shares. As a result, minority shareholders often lack adequate protection and are vulnerable to ownership dilution. The study concludes that there is an urgent need to reconstruct corporate legal norms in response to the growing practice of debt-based convertible financing. The author recommends that policymakers consider limiting the exceptions to the pre-emptive right and encourage contractual compensation schemes for minority shareholders as a more equitable form of protection within modern corporate structures.